Analysis of series connected photovoltaic thermal air collectors partially covered by semitransparent photovoltaic module. (1st November 2016) - Shyam,; Tiwari, G.N.
Highlights: Analytical expression for solar cell electrical efficiency has been derived. Annual performances and energy matrices on energy/exergy basis have been estimated. Uniform annualized cost of energy/exergy has been determined. Abstract: In the present work, an analysis for series connected photovoltaic thermal (PVT) air collectors has been done. The analytical expressions for efficiencies (electrical and thermal), air temperature, thermal energy and exergy, and electrical energy have been derived for two cases (Case A: inlet portion covered by semitransparent PV module and Case B: outlet portion covered by semitransparent PV module). The energy matrices, uniform annualized cost and carbon credits have also been estimated. It was found that, for lower mass flow rate and less number of series connected collectors, Case A gives better performance whereas at higher mass flow rate and large number of series connected collectors, both cases give similar results. The energy pay-back time for overall thermal energy saving was 1.12 years; and for exergy saving it was 7.72 years. For 30 years life time and 4% interest rate, the uniform annualized costs were 0.016 /kW h (for overall thermal energy saving) and 0.109 /kW h (for exergy saving).